Use of Photodynamic Therapy Associated with Antimicrobial Peptides for Bacterial Control: A Systematic Review and Meta-Analysis - Dias, Luana Mendonça [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Medeiros, Karine Sousa [UNESP]; Cilli, Eduardo Maffud [UNESP]; Pavarina, Ana Claudia [UNESP] (MDPI, 2022)
Considering the challenges related to antimicrobial resistance, other strategies for controlling infections have been suggested, such as antimicrobial photodynamic therapy (aPDT) and antimicrobial peptides (AMP). This study aims to perform a systematic review and meta-analysis to obtain evidence on the antimicrobial effectiveness of aPDT associated with AMP and establish in vitro knowledge on this topic for further study designs. The PubMed, Scopus, Web of Science, Science Direct, Scielo, and Cochrane Library databases were searched. Two independent and cal-ibrated researchers (Kappa = 0.88) performed all the systematic steps according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The odds ratio (OR) was used as the effect measure. The Peto method was used to perform the meta-analysis due to the sparse data. Twenty studies were included in the present review. The result was significant (OR = 0.14/ p = 0.0235/I-squared = 0%), showing better outcomes of aPDT associated with peptides than those of aPDT alone for controlling the microbial load. Only 20% of the studies included evaluated this approach in a biofilm culture. Combined treatment with aPDT and AMP highly increased the ability of microbial reduction of Gram-positive and Gram-negative bacteria. However, additional blind studies are required to evaluate the efficacy of this therapy on microbial biofilms.
Keywords: Anti-infective agents; Antimicrobial peptides; Photochemotherapy